Vertical jump and isometric strength in professional female basketball players: starter vs. non-starter comparison - Nieto-Acevedo, R.; García-Sánchez, C.; Cañadas-Garcia, E.; Romero-Moraleda, B.; Marquina Nieto, M.; Cabarkapa, D. (PLOS ONE, 2026)
This study examined whether differences in countermovement jump (CMJ) and isometric mid-thigh pull (IMTP) force-time metrics exist between starters and non-starters in professional female basketball players. Twenty-two athletes (7 starters, 15 non-starters) competing in the first Spanish basketball league completed CMJ and IMTP testing using dual force plate system. CMJ variables included jump height, peak and mean braking and propulsive force, time-to-takeoff, and net impulse. IMTP variables included peak force and rate of force development (RFD) at 0-100 and 0-250 ms. Independent t-tests and Hedges` g effect sizes were used to assess between-group differences. No statistically significant differences were observed between starters and non-starters for any CMJ or IMTP force-time metrics of interest (p > 0.05). Both groups displayed similar values in jump height, force production, and RFD, with effect sizes ranging from small to moderate (g = 0.04-0.49). However, starters were significantly older than non-starters (p = 0.018), while no differences were found in body mass and height (p > 0.05). Overall, the findings of the present study indicate that, at the professional level of play, CMJ and IMTP performance characteristics are not capable of distinguishing starters from non-starters in women`s basketball. Starting status may be shaped more by competitive experience, technical proficiency, and tactical awareness. Although monitoring neuromuscular performance remains valuable, player selection and role differentiation appear to depend more on skill execution and contextual game demands than on strength characteristics alone.